Music of the Eye, Music of the Ear - Secondulfo, Domenico (Italian Sociological Review, 2016)
The paper explores the concepts of Ear world and Eye world, according to McLuhan’s theory, applying them to the difference between classical music and popular music. Ear music is a world of more passionate sounds and close to the body. The Eye music is a world of sounds heavily influenced by technology and by the professionalization of the music. A difference that is close to that theorized by Durkheim between mechanical and organic solidarity. In the text there are several examples of the two types of music, also through telematic links.